MULTISYSTEM INFLAMMATORY SYNDROME ASSOCIATED WITH COVID-19 IN CHILDREN: ETIOPATHOGENESIS, CLINICAL PRESENTATION AND THERAPY - Krasic, Stasa; Bajcetic, Milica; Vukomanovic, Vladislav (Medicinski podmladak, 2023)
Multisystem inflammatory syndrome in children (MIS-C), associated with coronavirus disease-19 (COVID-19), is a life-threatening condition resulting from a cytokine storm and hyperinflammation in genetically predisposed children after a symptomatic or asymptomatic infection caused by SARS-CoV-2. The etiopathogenesis of this inflammatory disorder has yet to be clarified. However, endotoxemia and significant micro- and macrovascular damage lead to increased synthesis of reactive species, reduced availability, and/or increased consumption of antioxidants, disrupting redox homeostasis. Given the severe clinical picture and potentially life-threatening condition, early application of immunomodulatory therapy is necessary. Although clear recommendations for MIS-C therapy have not been made, IVIG and corticosteroids play a crucial role in treatment. In addition to being anti-inflammatory, IVIG has also been shown to have an antioxidant effect. At the same time, there is still no data on corticosteroids modulating the degree of oxidative stress in patients with MIS-C associated with COVID-19. However, the use of corticosteroids showed a rapid improvement in clinical findings, hematological and biochemical parameters, ECG records and echocardiographic findings in patients with MIS-C associated with COVID-19.
Keywords: MIS-C, COVID-19, oxidative stress, treatment